2018
DOI: 10.1038/s41598-018-23318-1
|View full text |Cite
|
Sign up to set email alerts
|

Delta-like 3 is silenced by HBx via histone acetylation in HBV-associated HCCs

Abstract: Hepatocellular carcinoma (HCC) is a common malignant tumor with poor prognosis. We previously showed that expression of Delta-like 3 (DLL3), a member of the family of Delta/Serrate/Lag2 ligands for the Notch receptor, is silenced by aberrant DNA methylation and that overexpression of DLL3 in an HCC cell line induces cellular apoptosis. However, how DLL3 expression is regulated during hepatocarcinogenesis is still unclear. Here, we show that silencing of DLL3 during hepatocarcinogenesis is closely related to vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…DLL3 is expressed in the cytoplasm of normal hepatocytes, but is silenced in HCC by DNA methylation and histone acetylation induced by the hepatitis B virus (HBV). 45 Histone deacetylase (HDAC) inhibitors such as TSA effectively restore DLL3 expression in HCC cells. The reactivation of DLL3 inhibits HCC cell growth and induces cell apoptosis independently of Notch1, suggesting that DLL3 has a tumor-suppressive role through Notch-independent mechanisms.…”
Section: Delta-like Ligands In Liver Cancermentioning
confidence: 99%
“…DLL3 is expressed in the cytoplasm of normal hepatocytes, but is silenced in HCC by DNA methylation and histone acetylation induced by the hepatitis B virus (HBV). 45 Histone deacetylase (HDAC) inhibitors such as TSA effectively restore DLL3 expression in HCC cells. The reactivation of DLL3 inhibits HCC cell growth and induces cell apoptosis independently of Notch1, suggesting that DLL3 has a tumor-suppressive role through Notch-independent mechanisms.…”
Section: Delta-like Ligands In Liver Cancermentioning
confidence: 99%
“…In other cancers types, our group proved that DLL3 was suppressed in HCC. 14 In contrast, the expression levels of DLL3 were increased in pancreatic ductal adenocarcinoma. 22 Therefore, the roles of DLL3 seem to depend on the cancer type.…”
Section: Discussionmentioning
confidence: 95%
“…Regardless of the data provided, the exact mechanism by which HBV proteins altered the early fate of the cells was still unclear. Several studies had shown that DNA demethylation could be a major mechanism in the increase of the expression of CSC markers in normal hepatocytes [29] , also correlated with HBV DNA integration [30] and the axis of HBx-DLL3 (Delta-like 3) of Notch receptor [31] . In the last study, the treatment of HBV-transformed cells with a histone deacetylase inhibitor induced DLL3 expression [31] .…”
Section: Hbvmentioning
confidence: 99%
“…Several studies had shown that DNA demethylation could be a major mechanism in the increase of the expression of CSC markers in normal hepatocytes [29] , also correlated with HBV DNA integration [30] and the axis of HBx-DLL3 (Delta-like 3) of Notch receptor [31] . In the last study, the treatment of HBV-transformed cells with a histone deacetylase inhibitor induced DLL3 expression [31] . In a recent 2018 study, it was shown that in the very early stage of HCC, the global DNA methylation 5hmC and 5fC contents were decreased significantly.…”
Section: Hbvmentioning
confidence: 99%